Evaluation of cnpt-direct assay and development of a modified cnpt-edta assay todifferentiatendm from oxa-48 like carbapenemases - KRISHNARAJU M; AGILA KUMARI P; BALAJI VEERARAGHAVAN; RAMA VAIDYANATHAN (International Journal of Pharma and Bio Sciences, 2016)
Infections caused by carbapenemase producing bacteria are a worldwide threat, due to their association with high mortality. Early diagnosis is the key to treatment and can help in preventing the spread of infection. In this study, we have evaluated the phenotypic assay, carbaNP test (CNPt)-direct, that is used to identify carbapenemase producers. We have introduced CNPt-EDTA direct, a modification of the (CNPt)-direct test. The CNPt-EDTA direct can be used to distinguish strong metallo carbapenemases producers such as the NDM enzyme from weak hydrolyzers such as the OXA-48 like enzymes.Thirty-one bacterial isolates, including twenty eight clinical isolates, two positive control strains and one negative control strain, were subjected to the CNPt- direct, and the CNPt-EDTA-direct assays. Based on the color produced(from red to yellow or orange), twenty seven clinical isolates tested carbapenemase positive by CNPt-direct, of which eighteen were strong carbapenemase hydrolyzers and nine weak hydrolyzers. Each isolate was then tested by CNPt-EDTA direct and confirmed by gene specific PCR. When analysed by the CNPt-EDTA-direct, the strong carbapenem hydrolysers showed that fourteen isolates harboured the NDM enzyme, while four harboured a strong hydrolyser in association with or without class B enzyme. Out of the nine weak hydrolysers, eight were EDTA insensitive and harboured the OXA-48 like enzyme and one harboured the VIM enzyme. Thus the use of CNPt-direct in conjunction with CNPt-EDTA direct is a cost-effective and sensitive method to identify and classify carbapenemases, especially the NDM and OXA-48 like enzymes.